Proses Pembelajaran Tahfizh Al-Qur’an Dalam Meningkatkan Hafalan Peserta Didik di Madrasah Tsanawiyah Negeri (MTSN) Padang Panjang - Asmul, Ali; Gestaria, Nita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research is motivated by the excellence of Tahfizh al-Qur'an learning at MTsN Padang Panjang by making tahfizh as an intracurricular subject, with the implementation of learning once a week but able to form students who memorize the Qur'an with a target of memorizing at least 1 juz within one year. Based on this background, the objectives of this study are: (1) to reveal how the planning of Tahfizh learning improves students' memorization (2) to reveal how the implementation of Tahfizh learning improves students' memorization (3) to reveal how the evaluation of Tahfizh learning improves students' memorization (4) to reveal the supporting and inhibiting factors of the Tahfizh learning process in improving students' memorization. The research method used by the author is a descriptive method, with a qualitative approach while the data sources in this study are the main data sources (primary) namely the tahfizh teacher, tahfizh coordinator, all students of MTsN Padang Panjang, while secondary data are the curriculum representative, student representative and the head of MTsN Padang Panjang. The research results obtained by the author include: (1) teacher planning before learning (2) learning carried out in accordance with the RPP, namely with tahfizh learning carried out using the wahdah method, sima'i, ardhul qira'ah (deposit system), the partner method and the muraja'ah method. (3) learning evaluations in the form of daily, weekly, mid-semester, semester and annual, namely in the form of tahfizh graduations attended by students who have memorized at least 1 juz. (4) supporting factors for tahfizh learning are internal (seriousness, intelligence, interest and talent, high self-readiness and motivation) and external factors (family support, guidance from mentors, motivation from peers and big rewards). The inhibiting factors are the study schedule which is too tight and some memorizing due to the demands of the madrasah.